Development of Renewable Energy–Based Electrical Instructional Media to Improve Vocational Students’ Applied Science Concept Understanding - Yusnidah (Postgraduate, University of Mataram, 2026)
This study aimed to develop renewable energy–based electrical instructional media in the form of a practicum kit and an e-module and to examine their feasibility and effectiveness in improving applied science concept understanding among vocational students. The study employed a Research and Development approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The instructional media were validated by 2 expert reviewers to assess content suitability, instructional design, technical quality, and media integration. The effectiveness of the media was evaluated through a pretest–posttest design involving 28 students of a Diploma (D3) Technika program. Data were analyzed descriptively, and learning improvement was measured using the normalized gain (N-gain). The results showed that the developed practicum kit and e-module achieved a very feasible category based on expert validation, with an average validation score of 88%. Furthermore, students' applied science concept understanding improved after using the instructional media, as indicated by an N-gain in the medium category (0.59). Students also provided very positive responses toward the usability and relevance of the media. These findings indicate that renewable energy–based practicum kits and e-modules are feasible and effective instructional media for supporting applied science learning in vocational electrical education, contributing to the enhancement of practical skills and theoretical understanding in the D3 Technika curriculum.